Formação do pedagogo: concepções históricas, identidade e formação humana - Müller, Luciane dos Santos (2017)
The theme of this thesis lies in the area of teaching training, whis the study of the historical concepcions on identity and human formation. The research that gave origin is analytical in nature, bibliographical hermeneutics, backed by legal documents, namely, opinions, decrees and laws that regulated the profession of the educator, critical texts of respected authors and other bibliographic references that give support to the development of a perspective of humanizing Pedagogy course. Its goals are: to investigate the challenges of teacher training for a human formation; analyze the periods of history, from the legal regulations concerning the formation of the pedagogue, and the main theoretical referential that guided the role of a trader; and get the pillar to the strengthening of the status of your teacher and educational activities for human training. The paper analyzes the understandings and senses expressed in the documents that have guided the design of the course of pedagogy, clarifies the intended purpose the formation of the educator in different opinions and guidelines and reconstructs some of the main criticisms that the course as received significant educational researchers, like Brzezinsk, Libâneo and Silva. The reflection is made on the course has as literaryphilosophical works, reference as those of Fabre, Goergen, Flickinger and Dalal, who has pointed to important ideas about the status of the course in pedagogy and the need for her to develop an expanded notion of education in perspective of humanizing and critical education. Outlines a thought about the historical process of the Constitution, which expresses the different identities he has assumed in the course of your history and, at the same time, identifies the future prospects which feature both in curricular guidelines as in literature. Describes the changes in professional teacher identity, seeking your teaching roleother approaching prospects. It is concluded that the formation of the educator must come accompanied by a vision of human formation and reflective education. There is also the need for an expanded definition of pedagogy and training today, more emancipatory, supported in dialogue, care of themselves and the opening to the other.